The Instructional Design Of Teaching Writing Skill At English Department Of Ums In 2013/2014 Academic Year: A Naturalistic Study - Anindyawati, Fibrian; , Prof. Dr. Endang Fauziati; , Agus Wijayanto Ph, D. (2014)
The objective of this research is to get a clear description of the teaching learning process of Writing I-Writing IV Skill at English Department of Muhammadiyah University of Surakarta in which covers about the syllabuses, the learning objectives, the instructional materials, the teachers' roles, the students' roles, the differences of classroom techniques, the differences of classroom procedures, the teaching media in the teaching learning process, and the assessment models in teaching learning process. The data of this research were collected from several technique including observation, interview and documentation. This research was conducted in naturalistic study. The syllabus used in Writing I and Writing II is grammatical syllabus and the syllabus used in Writing III and Writing IV is task-based syllabus. The learning objectives categorized into two namely, general objectives and specific objectives. The instructional materials were divided into three categories: printed materials, visual materials, and materias taken from internet. The teachers' roles were divided into five: as an organizer, as a consultant, as a feedback provider, as an assessor, and as a motivator, while the students' role were divided into three: as an active participant, as a peer reviewer, and as a peer editor. The classroom techniques consist of: brainstorming, discussion about the theories, question and answer exercises, getting students to self-correct, and assignment. The classroom procedures of Writing I and II are BKOF-MOT-ICOT; the classroom procedures of Writing III are reviewing, gathering ideas, organizing, build writing activity; and the classroom procedures of Writing IV are reviewing, explaining the materials, gathering ideas, organizing, build writing activity. The media used by the lecturers are LCD Projector, board, slides, and videos. The lecturers used some kinds of assessment model consist of: multiple choices, weekly assignments, quizzes, mid-test, and final-test. The researcher found some strengths and weaknesses after conducted the research. The strengths come from the lecturers and the students. The lecturers could make a comfortable atmosphere in writing class the students also active and responsive toward the lecturers. However, it also shows the weaknesses. The first is the classroom situation which crowded and noisy, and the students character who did not have self-confidence in writing